2008
DOI: 10.1097/01.nnr.0000313498.17777.71
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing and Patient Mortality in Intensive Care Units

Abstract: Nurse and physician staffing and specialization of ICUs impacted patient mortality. Associations differed in tertiary and secondary hospitals. Further investigation of the impact of organizational environments in ICUs is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 27 publications
5
78
0
2
Order By: Relevance
“…Cho et al 39 investigated the deleterious effect of lower nurse staffing levels in a large Korean study with 27 372 patients from 42 tertiary and 194 secondary hospitals. Compared with a ratio of 2 patients to 1 nurse, each 1-patient increase in the ratio was associated with a 9% increase in the odds of death (OR, 1.09; 95% CI, 1.04 to 1.14).…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al 39 investigated the deleterious effect of lower nurse staffing levels in a large Korean study with 27 372 patients from 42 tertiary and 194 secondary hospitals. Compared with a ratio of 2 patients to 1 nurse, each 1-patient increase in the ratio was associated with a 9% increase in the odds of death (OR, 1.09; 95% CI, 1.04 to 1.14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies available in international literature correlated the number of nursing hours with the quality of care delivery, concluding that the larger number of care hours nurses deliver is associated with lower mortality and adverse event rates, as well as with the drop in mortality rates deriving from these events (18)(19)(20)(21) .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of staff shortages can be seen on patient health outcomes, particularly in the ICU, where fewer nurses per patient can result in increased mortality. [78] Studies specifically looking at populations of healthcare workers have also found evidence of vaccine effectiveness, as well as a possible decrease in absenteeism among vaccine recipients. A 3-year RCT of TIV in young healthy HCWs in Baltimore, using serologically confirmed influenza infection as an outcome measure, estimated a VE of 88% for influenza A and 89% for influenza B.…”
Section: Disease Burdenmentioning
confidence: 99%
“…Review of studies on safety of TIV in children did not reveal any evidence for important safety concerns [157], in particular no evidence of an increased risk of febrile convulsion. [78] In clinical trials, an increased risk for wheezing post-vaccination was observed in LAIV recipients aged <24 months. [182,189] An increase in hospitalizations also was observed in children aged <24 months after vaccination with LAIV.…”
Section: Vaccine Safetymentioning
confidence: 99%